Pengaruh Abdominal Lifting Dan Counter Pressure Terhadap Penurunan Tingkat Nyeri Persalinan Kala I : Literature Review - Sita Wati (STIKES Citra Delima Bangka Belitung, 2023)
Labor pain is a major problem experienced by maternity mothers which, if not handled properly, can increase anxiety or worry to depression and have an effect on increasing adrenaline hormones affecting maternal cardiac output and decreased uteroplacental perfusion and can cause prolonged labor. One of the steps to reduce labor pain is to use abdominal lifting and counter pressure techniques which are categorized as safe and quite effective interventions. The purpose of this study was to determine the effect and effectiveness of abdominal lifting and counter pressure in reducing labor pain in the first stage of normal delivery. This study is a systematic literature review using secondary data obtained from research results by previous researchers. Literature search using several databases such as Google Scholar, PUBMED and Sci-Hub. Based on the results of article screening, 13 articles were obtained according to the inclusion criteria, consisting of 10 national journals and 3 international journals spanning the last 5 years, from 2018-2022. A total of 11 journals with a quasi-experimental design and 2 other pre-experimental designs with the overall research subjects used were first-stage maternity mothers. Based on the results of the review, there is a difference between before and after the intervention, namely a decrease in the level of pain felt by maternity after giving Abdominal lifting and counterpressure therapy. So it can be concluded that these two techniques have influence and effectiveness in reducing pain during labor.